A importância da brincadeira no desenvolvimento infantil: uma análise à luz da BNCC - Castro, Daniela Gomes de (Universidade Federal de São Carlos, 2025)
This study aims to analyze the importance of play in early childhood development in light of the guidelines established by the Brazilian National Common Curricular Base (BNCC). It is based on the understanding that play is an essential activity for knowledge construction, the development of socio-emotional skills, and the child’s holistic formation. The research is qualitative in nature, with an exploratory and descriptive approach, and is primarily grounded in a literature review of authors who discuss playfulness and child development, such as Vygotsky, Piaget, and Kishimoto. The study reflects on different types of play and how the intentional planning of playful situations by educators can enhance meaningful learning. The results reinforce the BNCC’s guidance that play should be valued as a core element of pedagogical practice, contributing to children is cognitive, emotional, motor, and social development.
The importance of play in child development: an analysis in light of the BNCC
Keywords: Brincadeira; Educação infantil; Desenvolvimento infantil; BNCC; Ludicidade; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM